Diseño de un plan de marketing para fomentar el turismo de la parroquia rural Tocachi ubicada en el cantón Pedro Moncayo en la provincia de Pichincha - Suárez Cabascango, Laura Stefany (2015)
This paper titration is designing a marketing plan to promote tourism of the Rural Parish Tocachi as this has variety of natural attractions that can be exploited by tourism, is why it is considered important to deepen the concepts covering the marketing and community tourism. It also highlights the legal aspects, as both the Constitution of Ecuador and Regulation for Community Tourism Centers support the initiative for the development of tourism activities, driven by indigenous communities, peasants and Afro for economic development. The executed situational diagnosis begins with a microenvironmental studio where you can learn in depth the history of the parish and thereby detect the sights that can potentiate, continuing a macroambietal study, which will help meet the demographic, economic, natural forces, technological , political and cultural place.